Is cytotoxicity a determinant of the different in vitro and in vivo effects of bioactives? - Mattia Di Nunzio; Veronica Valli; Lidia Tomás-Cobos; Teresa Tomás-Chisbert; Lucía Murgui-Bosch; Francesca Danesi; Alessandra Bordoni (BMC, 2017)
Abstract Background Foodstuffs of both plant and animal origin contain a wide range of bioactive compounds. Although human intervention studies are mandatory to assess the health effects of bioactives, the in vitro approach is often used to select the most promising molecules to be studied in vivo. To avoid misleading results, concentration and chemical form, exposure time, and potential cytotoxicity of the tested bioactives should be carefully set prior to any other experiments. Methods In this study the possible cytotoxicity of different bioactives (docosahexaenoic acid, propionate, cyanidin-3-O-glucoside, protocatechuic acid), was investigated in HepG2 cells using different methods. Bioactives were supplemented to cells at different concentrations within the physiological range in human blood, alone or in combination, considering two different exposure times. Results Reported data clearly evidence that in vitro cytotoxicity is tightly related to the exposure time, and it varies among bioactives, which could exert a cytotoxic effect even at a concentration within the in vivo physiological blood concentration range. Furthermore, co-supplementation of different bioactives can increase the cytotoxic effect. Conclusions Our results underline the importance of in vitro cytotoxicity screening that should be considered mandatory before performing studies aimed to evaluate the effect of bioactives on other cellular parameters. Although this study is far from the demonstration of a toxic effect of the tested bioactives when administered to humans, it represents a starting point for future research aimed at verifying the existence of a potential hazard due to the wide use of high doses of multiple bioactives.